Adaptive computation for elastic wave propagation in plate/shell structures under moving loads - Tie, Bing; Aubry, Denis; Boullard, Arnaud (European Journal of Computational Mechanics, 2003)
An adaptive remeshing method tailored to computations for elastic wave propagation is proposed and its application to the elastic wave propagation in plates or shells under moving loads is presented. The method is defined within the framework of the space-time discontinuous Galerkin method, which is particularly suitable for dealing with adaptive meshes that change in time. An a priori theoretical wave propagation analysis is done to determinate an appropriate element size, then the mesh adaption strategy consists of refining finite elements according to this size in zones where local unbalanced residuals are large. The plate/shell structures are modelled with Mindlin kinematics and the dispersive phenomenon of bending waves is considered. The pertinence of the Kirchhoff-Love and Mindlin kinematical models with respect to frequency ranges and plate/shell thickness is discussed. Numerical examples are given to illustrate the interest of the adaptive method.